The actuality of Paulo Freire in times of pandemic: weaking dialogues about the challenges of education and teaching (Práxis Educativa, 2020)
In this article, at a time when we celebrate Paulo Freire’s centenary, we discuss the current moment crossed by profound crises. We problematize this context, especially with regard to the Brazilian educational scenario that experiences pressures for remote education in times of pandemic, looking in Freire’s legacy for clues to understand and seek answers to what we have lived and faced. We articulate Freire’s reference to the experiences lived by the Municipal Reference Center for Youth and Adult Education (Centro Municipal de Referência de Educação de Jovens e Adultos - CREJA), to the teaching work, tensioned by conservative projects, and the movement of lives understood in their potential for approximation and reflection in times of social distancing. We understand that revisiting Paulo Freire and having a dialog with his concepts is urgent and necessary, in the thickening for the densification of our actions and investigations in teacher education.Keywords: Paulo Freire. Pandemic. Education.